Equity, diversity, and inclusion in the construction of journalistic and training agendas for peace in Colombia - Páez Valdez, Julián Enrique; Rendón Cardona, Paula Andrea; Betancurth Becerra, Carlos Mario; Aristizábal, César Alberto; García Ruiz, Johanna (Frontiers in Education, 2023)
Since their early stages, developing narratives has been characteristic of human beings, allowing them to create community and generate cohesion—one that has endured for thousands of years is ‘peace’. However, in some territories, excessive ambition, fear imposed by force, and power over laws have proliferated. In the case of Colombia, war as an industry, empowers different sides that are either endorsed or rendered invisible in the narratives of traditional mass media, media content has always favored war journalism and neglected two vital approaches: peace journalism and university journalism. This study’s relevance lies in its use of big data, automated lexicometry, and statistical discourse analysis to understand how university journalism built a peace journalism agenda, taking the narrative of the Peace Agreement in Colombia, as a framework of observation, with a clear result on the importance of equity, diversity and equality in a peaceful transition scenario in Colombia. The study reveals that university journalism has a diverse narrative approach, focusing on presenting the social problems and inequities, the lack of political capacities within communities, the need for a transitional approach towards peace, and the pursuit of truth. The study used mixed research techniques where students narrated their individual perspectives that informed a collective view by integrating the voice of those who suffer the conflict daily. Simultaneously, they showed how academia, from its training function, develops exercises that may compromise the integrity of the axiological values of communication and journalism. The main implication of our study suggests the need to strengthen pedagogical processes of peace in the curriculum and training that enable the next generation of journalists in the country to potentially shift their discourse towards peace journalism and divergent solutions, as opposed to those proposed by traditional media. In conclusion, including youth opinions that were supported by experts of the process introduced an element of community empowerment and recognition of victims within the context and social structure of the Colombian conflict.